Les pays sous-developpes géographie, 6ème secondaire - Mudindambi, Kama Funzi (Serenite, 1983)
Under-developed Countries. A pedagogical text designed to help professors teach about underdeveloped countries in Africa, Asia and South America. In addition to providing information on the demographics and general economic trends in each of these three continents, it also includes 3-4 specific country studies from each continent. Underlying the text is the argument that "underdeveloped countries have tremendous natural and human resources and, despite difficulties, they can grow if, on the basis of popular political will, they organize their economy with an eye to national interest." -- Introduction (translated)